2004
DOI: 10.1007/s00339-003-2313-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic surface structure of n -ML Ag/Cu(111) and Cs/ n -ML Ag/Cu(111) as investigated by 2PPE and STS

Abstract: We investigated the electronic structure of epitaxially grown silver films on Cu(111) with and without adsorption of cesium by means of scanning tunneling spectroscopy and two-photon photoemission. This system has been chosen as a model system to engineer and measure the dynamics of charge-transfer processes between an adsorbate and a heterogeneous substrate. Special emphasis has been laid on the investigation of the energy shift of the Shockley-type surface state and an excited cesium resonance as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Even if the energy position of the spectral feature in the h-BN islands is similar in both systems, there is a large difference in the onset on the Ag/Cu(111) areas with respect to the bare silver. Previous work has shown that the Ag film thickness on Cu(111) determines the energy shift of the Shockley-type surface state [47]. Accordingly, we conclude that the copper surface is covered by 3 ML of silver (see Fig.…”
Section: B Spectroscopic Characterizationmentioning
confidence: 64%
See 1 more Smart Citation
“…Even if the energy position of the spectral feature in the h-BN islands is similar in both systems, there is a large difference in the onset on the Ag/Cu(111) areas with respect to the bare silver. Previous work has shown that the Ag film thickness on Cu(111) determines the energy shift of the Shockley-type surface state [47]. Accordingly, we conclude that the copper surface is covered by 3 ML of silver (see Fig.…”
Section: B Spectroscopic Characterizationmentioning
confidence: 64%
“…Table I (111), spatially modulated following the moiré superstructure (−0.84 eV in the valleys and −1.14 eV on the hills) [28]. Once the silver intercalates, the surface state band minimum is shifted smoothly to higher values in the Ag/Cu(111) areas (e.g., at −235 mV for 3 ML of Ag) [47]. On the h-BN regions, the surface state depopulates and the band onset appears at similar energies as for h-BN It is interesting to note that the Ag thickness allows us to tune the properties of the system in a controlled manner.…”
Section: Discussionmentioning
confidence: 99%
“…STM and LEED measurements show a (9 Â 9) reconstruction for 1 ML Ag [306][307][308][309][310][311][312][313][314]. Also for this system, ARPES experiments [312,[315][316][317][318] have revealed the existence of well-defined Ag 5sp-derived QWS even for rather high film thickness, with subsequent significant changes in the dynamical screening properties with respect to the case of Ag single crystals. Due to the presence of a surface projected energy gap in the Cu(1 1 1) band structure, QWS on Ag/Cu(1 1 1) are characterized by standing wave patterns [314], while on the contrary standing waves are not supported on Ag/ Ni(1 1 1) due to fact that Ag QWS do not arise within the energy gap of Ni(1 1 1).…”
Section: Excitation Of S à P Sp and Of The Mpmentioning
confidence: 86%
“…Since the centroid of this band lays above E F , the surface state shifts upward in energy with respect to its position in unstrained Cu(111) crystals. As the film thickness increases, the structural distortions in the topmost Cu layers attenuate and, correspondingly, the energy shift decreases (see the discussion on the surface properties of the Ag/Cu(111) system in [32]). …”
mentioning
confidence: 99%